An unusual cause of hypoxia: getting to the heart of the matter. Issue 1 (March 2018) - Hammersley, Daniel; Shamsi, Aamir; Zaman, Mohammad Murtaza; Berry, Philip; Sturridge, Lydia
Abstract : A 63-year-old female presented to hospital with progressive exertional dyspnoea over a 6-month period. In the year preceding her admission, she reported an intercurrent history of abdominal pain, diarrhoea and weight loss. She was found to be hypoxic, the cause for which was initially unclear. A ventilation–perfusion scan identified a right-to-left shunt. Transoesophageal echocardiography (TOE) demonstrated a significant right-to-left intracardiac shunt through a patent foramen ovale (PFO); additionally severe tricuspid regurgitation was noted through a highly abnormal tricuspid valve. The findings were consistent with carcinoid heart disease with a haemodynamically significant shunt, resulting in profound systemic hypoxia. 24-h urinary 5-hydroxyindoleacetic acid (5-HIAA) and imaging were consistent with a terminal ileal primary carcinoid cancer with hepatic metastasis. Liver biopsy confirmed a tissue diagnosis. The patient was commenced on medical therapy for carcinoid syndrome. She subsequently passed away while undergoing anaesthetic induction for valvular surgery to treat her carcinoid heart disease and PFO. Learning points: Carcinoid syndrome is a rare condition, which presents a significant diagnostic challenge due to its insidious presentation and symptoms. This frequently results in a marked delay in diagnosis. Carcinoid heart disease is characterised by distortion and fixation of right-sided heart valves, which cause valvular regurgitation, stenosis or both. Valvular abnormalities are often found in association with right ventricular failure. In the case described, carcinoid heart disease was found in association with a significant right-to-left intracardiac shunt, created through a PFO due to right atrial volume overload. This prevented right ventricular failure at the expense of creating a state of severe induced systemic hypoxia. This physiological adaptation resulted in an unusual presentation of this condition, due to symptoms resulting from hypoxia, rather than the classical symptoms of carcinoid syndrome or right ventricular failure.